(untitled) (Journal of Atomic and Molecular Sciences, 2013)
At ab initio level, time-dependent hybrid density functional theory and response theory have been applied to study the solvent effect on the geometrical and elctronic structure as well as one- and two-photon absorption (TPA) properties of 2,2':6',2"-terpyridine-based chromophore L. It is found that solvatochromic shift of charge-transfer (CT) appears nonmonotonic behavior with regard to the polarity of solvent. Besides, the one-photon absorption (OPA) strengths are enlarged slightly and are more dependent on the optical dielectric constant. The TPA cross sections are enhanced when considering solvent effect compared to that in gas phase and the TPA cross sections show an increasing trend with the increase of solvent polarity. All the theoretical results are in reasonable agreement with experimental data.